Self-Efficacy And Parenting Styles As Correlates Of Social Anxiety Disorder Among Secondary School Adolescents In Obio/Akpor LGA Of Rivers State - Ekechukwu, R. O. (Advances in Social Sciences Research Journal, 2019)
The study investigated self-efficacy and parenting styles as correlates of social anxiety disorder among secondary school adolescents in Obio/Akpor LGA of Rivers State. The study adopted the correlational research design. The study used a sample of 300 students who were independently selected using simple random sampling technique. Three instruments were used to collect data for the study, they included; Social Anxiety Disorder Scale, Self-efficacy Scale and Parenting Styles Scale. The study was guided by two research questions as well as two corresponding hypotheses. The data was analyzed with mean, standard deviation and independent sample t-test. The findings of the study revealed that, low self-efficacy authoritative and authoritarian parenting styles significantly predicted social anxiety disorder among secondary school adolescents in Obio/Akpor LGA of Rivers State. Based on the findings of the study it was recommended among others that counseling for adolescents with social interaction anxiety should be encouraged in schools with aim of improving students’ interactional skills.